Shelf Fluvial Paleo Structures: Seabed Seismic Acoustic View - Klyuev, Mikhail; Schreider, Anatoly; Zverev, Alexey (Cham : Springer Nature Switzerland : Imprint: Springer, 2023)
The book considers the riverine paleo structures of the coastal marine zone from the point of view of marine bottom seismic acoustics. The authors describe the mechanisms of the origin and features of riverine paleo structures in the coastal marine area. The methods applied for this kind of research have been developed and explained comprehensively, including geomorphology and interpretation of seismic acoustic facies. Besides, the authors also propose a classification of morphological features, signs and technology of recognition, as well as methods for mapping of coastal river facies supported by an extensive list of literary sources is given. The book will be of interest to marine geophysicists, marine geologists, and those interested in new methods to approach marine problems worldwide.
Origin of fluvial paleo-structures of the shelf -- Seismic-acoustic methods for paleo-channel studies -- Shelf paleo-channel structures from broadband continuous seismic-acoustic profiling -- Recognition principles, detection technology and mapping of paleo-channels -- Apparatus for broadband seismic-acoustic surveys of shelf fluvial paleo-structures -- Conclusion -- Literature.
Keywords: Oceanography; Natural disasters; Geology; Geophysics; Sedimentology; Ocean Sciences; Natural Hazards; Geology; Geophysics; Sedimentology